Velar activity in individuals with velopharyngeal insufficiency assessed by acoustic rhinometry - Inge Elly Kiemle TRINDADE; Bruna Mara Adorno Marmontel ARAÚJO; Ana Claudia Martins Sampaio TEIXEIRA; Andressa Sharllene Carneiro da SILVA; Ivy Kiemle TRINDADE-SUEDAM (University of São Paulo, 2014)
Acoustic rhinometry is routinely used for the evaluation of nasal patency. Objective: To investigate whether the technique is able to identify the impairment of velopharyngeal (VP) activity in individuals with clinical diagnosis of velopharyngeal insufficiency (VPI). Methods: Twenty subjects with repaired cleft palate and inadequate velopharyngeal function (IVF) and 18 non-cleft controls with adequate velopharyngeal function (AVF), adults, of both genders, were evaluated. Area-distance curves were obtained during VP rest and speech activity, using an Eccovision Acoustic Rhinometry system. Volume was determined by integrating the area under the curve at the segment corresponding to the nasopharynx. VP activity (ΔV) was estimated by the absolute and relative differences between nasopharyngeal volume at rest (Vr) and during an unreleased /k/ production (Vk). The efficiency of the technique to discriminate IVF and AVF was assessed by a ROC curve. Results: Mean Vk and Vr values (±SD) obtained were: 23.2±3.6 cm3 and 15.9±3.8 cm3 (AVF group), and 22.7±7.9 cm3 and 20.7±7.4 cm3 (IVF group), corresponding to a mean ΔV decay of 7.3 cm3 (31%) for the AVF group and a significantly smaller ΔV decay of 2.0 cm3 (9%) for the IVF group (p<0.05). Seventy percent of the IVF individuals showed a ΔV suggesting impaired VP function (below the cutoff score of 3.0 cm3 which maximized both sensitivity and specificity of the test), confirming clinical diagnosis. Conclusion: Acoustic rhinometry was able to identify, with a good discriminatory power, the impairment of VP activity which characterizes VPI.